Nambu-Goto Strings viaWeierstrass Representation - kotb, Mahmoud (JOURNAL OF ADVANCES IN PHYSICS, 2017)
A description of string model of gauge theory are related to minimal surfaces. notations of minimal surface and related mean and Gauss curvature discussed. The Weierstrass representation for a surface conformally which immersed in R used to represent Nambu- Goto action, action of Nambu Goto is calculated usingWeierstrass representation which can be used to calculate the Partion Function and potential, then a non-perturbative solution for action is aimed and fulfilled and a consequences of that are investigated and its mathematical and physical properties are discussed.